Investigation of State and Trait Anxiety Level of Athletes Participating in Archery Competitions - Saylam, Diyar Kaya; Alp, Hulusi (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2021)
Present study aimed to examine the state and trait anxiety levels of athletes engaged in archery competitions in terms of some variables. The research was carried out by using cross-sectional scanning model, which is one of the descriptive research approaches. The research population consisted of the athletes who participated in the Archery Championships. The sample of the research consisted of a total of 142 athletes, 59 women and 83 men, who voluntarily agreed to participate in the research among the athletes participating in the Championship. In the research, data were collected via Spielberger’s Trait-State Anxiety Inventory. The data were analyzed by SPSS 23. Since the data did not show normal distribution, analysis was performed using non-parametric tests. Kruskal Wallis test was used in multiple comparisons and Mann Whitney-U test was used in comparisons between the two variables. Significance level was taken as p <0.05. According to the analyzed results, there was no significant difference between the state and trait anxiety levels of the athletes in terms of gender, category, year of doing sports and number of participation in the tournament (p> 0.05) however, there were significant differences according to age and education variables (p <0.05).